Floculation With Prolongation Properties of Sulfur Microparticles by Anionic Polyacrylamide in A Flow - A.A. Kholmuminov; Sh.E. Khalilov (Genius Journals, 2022)
The possibility of using rheological approaches for flocculation of sulfur microparticles with anionic polyacrylamide in a longitudinal field in a free jet mode and a shear field generated in a sphere-plane system cell has been studied. It is shown that in a free jet, the "jet-aerosol" transition of a suspension based on S:PAA:water (1:0.1:100) and flocculated particles are realized with the prolongation property of the insecticide. В случае shear flow of a suspension based on S:PAA:water (1:1:50) in a “sphere-plane” cell, the rotating sphere transformed the gel-like suspension from the rheometer reservoir onto the surface in a thin layer. The formed layer with a thickness of about 0.5 mm had a gel-like appearance, which turned into a solid phase layer within 3 months as a result of the evaporation of water from the gel composition under normal condition
Keywords: polyacrylamide; free; hydrolyze; flocculant